Direct observation of electron emission from grain boundaries in CVD diamond by PeakForce-controlled tunnelling atomic force microscopy. (November 2015) - Harniman, Robert L.; Fox, Oliver J.L.; Janssen, Wiebke; Drijkoningen, Sien; Haenen, Ken; May, Paul W.
Abstract: A detailed investigation of electron emission from a set of chemical vapour deposited (CVD) diamond films is reported using high-resolution PeakForce-controlled tunnelling atomic force microscopy (PF-TUNA). Electron field emission originates preferentially from the grain boundaries in low-conductivity polycrystalline diamond samples, and not from the top of features or sharp edges. Samples with smaller grains and more grain boundaries, such as nanocrystalline diamond, produce a higher emission current over a more uniform area than diamond samples with larger grain size. Light doping with N, B or P increases the grain conductivity, with the result that the emitting grain-boundary sites become broader as the emission begins to creep up the grain sidewalls. For heavy B doping, where the grains are now more conducting than the grain boundaries, emission comes from both the grain boundaries and the grains almost equally. Lightly P-doped diamond samples show emission from step-edges on the (1 1 1) surfaces. Emission intensity was time dependent, with the measured current dropping to ∼10% of its initial value ∼30 h after removal from the CVD chamber. This decrease is ascribed to the build-up of adsorbates on the surface along with an increase in the surface conductivity due to surface transfer doping.